2005
DOI: 10.1007/s11136-004-3288-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of mothers of children with leukemia in Japan

Abstract: Mothers of children with leukemia requiring hospital care have poor HRQOL, particularly with regard to mental health and social functioning, and are at a greater risk for depression. These results suggest that the current system for treating leukemic diseases of children in Japan should also include close monitoring of mothers' mental health, and provision of appropriate treatment and psycho-social support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
0
11

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 17 publications
10
62
0
11
Order By: Relevance
“…The control group showed higher scores than the present in all domains. The findings were also similar to a study involving mothers to children with leukemia and a control group in Japan, which appointed lower scores on all SF-36 domains than in the control group, with statistically significant results in 5 out of 8 domains: physical role functioning, general perceived health, vitality, emotional role functioning and mental health (20) .…”
Section: Discussionsupporting
confidence: 86%
“…The control group showed higher scores than the present in all domains. The findings were also similar to a study involving mothers to children with leukemia and a control group in Japan, which appointed lower scores on all SF-36 domains than in the control group, with statistically significant results in 5 out of 8 domains: physical role functioning, general perceived health, vitality, emotional role functioning and mental health (20) .…”
Section: Discussionsupporting
confidence: 86%
“…Sin embargo, en este estudio no resultaron significativas las correlaciones del tiempo de cuidado con estas variables; esto en coincidencia con Rubira et al (24,50) . Las discrepancias posiblemente se deban a que en cuidadores de niños con cáncer se ha observado esta relación con la calidad de vida y no con trastornos emocionales específicos como los que se evaluaron en el presente estudio (15,25,(57)(58)(59)(60)(61)(62) . Las áreas que más se han afectado en la vida de los cuidadores de la muestra evaluada coinciden con el hecho de que la enfermedad del paciente impacta en la vida familiar, principalmente al aumentar las demandas del cuidador se alteran sus tareas domésticas y la relación que tiene con los otros hijos y con la pareja, lo cual ocasiona redistribución de roles, dificultades en la comunicación, alteraciones en las relaciones sexuales, distanciamientos e incluso infidelidades.…”
Section: Discussionunclassified
“…leukemia and cerebral palsy. 21,29 Limitations in daily activities (e.g. working or studying) could be caused by frequent hospital visits, acute painful crises and all other tasks associated with the responsibility of caring for a chronically ill child.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in caregivers of children with various chronic illnesses have shown that such caregivers report an impaired QoL compared to that of caregivers of healthy children. [18][19][20][21][22] We hypothesized that caregivers of children with SCD have a lower QoL compared to that of the healthy Dutch female population and caregivers of healthy children with the same SES.…”
Section: Introductionmentioning
confidence: 99%